Relating sequence encoded information to form and function of intrinsically disordered proteins. (June 2015) - Das, Rahul K; Ruff, Kiersten M; Pappu, Rohit V
Highlights: Compositions of IDPs fall into distinct classes. Compositional classes encode preferences for distinct conformational classes. Functions of disordered proteins are governed by composition-to-conformation relationships. Sequence patterning of oppositely charged residues can alter conformational properties. Charge patterning can directly impact IDP functions. Abstract : Intrinsically disordered proteins (IDPs) showcase the importance of conformational plasticity and heterogeneity in protein function. We summarize recent advances that connect information encoded in IDP sequences to their conformational properties and functions. We focus on insights obtained through a combination of atomistic simulations and biophysical measurements that are synthesized into a coherent framework using polymer physics theories.